Optimal control of microgrid by decentralized controller - Subhashree, A; Thenmalar, K; Deepa, K (International Journal of Engineering and Technology, 2018)
The Microgrid is modern small range of centralized electricity system. It achieves specific local goal such as reliability, carbon emission reduction, diversification of energy sources, and cost reduction. Microgrids are an ideal way to integrate renewable sources. The Microgrid is motivated by many factors such that , the need to integrate more renewable power to mitigate the global warming., increasing interest in connecting more Distribution Generation as a way to postpone large investment in transmission and bulk generation and the need to increase the reliability of the power system overall to minimize distribution losses. In microgrid the power generation is mainly depends on renewable energy sources. The renewable sources are unpredictable, so to maintain the system stability in uncertain environment is very difficult. During the changes in microgrids, it is to satisfy the demand with minimum tracking time and to stabilize the system. In order minimize the tracking time for attaining the system stability, robust PID control method is proposed. The simulation has been done in MATLAB/Simulink with required formulation.